A Role of 3-D Surface-from-Motion Cues in Motion-Induced Blindness. (December 2013) - Rosenthal, Orna; Davies, Martin; Davies, Anne M Aimola; Humphreys, Glyn W
Motion-induced blindness (MIB), the illusory disappearance of local targets against a moving mask, has been attributed to both low-level stimulus-based effects and high-level processes, involving selection between local and more global stimulus contexts. Prior work shows that MIB is modulated by binocular disparity-based depth-ordering cues. We assessed whether the depth effect is specific to disparity by studying how monocular 3-D surface from motion affects MIB. Monocular kinetic depth cues were used to create a global 3-D hourglass with concave and convex surfaces. MIB increased for stationary targets on the convex relative to the concave area, extending the role of 3-D cues. Interestingly, this convexity effect was limited to the left visual field—replicating spatial anisotropies in MIB. The data indicate a causal role of general 3-D surface coding in MIB, consistent with MIB being affected by high-level, visual representations.